2021
DOI: 10.3390/su13010343
|View full text |Cite
|
Sign up to set email alerts
|

Self-Perceptions on Digital Competences for M-Learning and Education Sustainability: A Study with Teachers from Different Countries

Abstract: The current international landscape shows that the most common alternative for the continuity of formative learning processes during the coronavirus pandemic has been the use the of e-learning to support children’s learning in environments outside of school. This forced change in teaching methods has consolidated the recognition that the digital skills of teachers are a relevant factor for the sustainability of education, both during the pandemic and in a future post-pandemic period or in other emergencies. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 20 publications
1
20
1
5
Order By: Relevance
“…This study aimed to investigate university students' perceptions towards the rapid passing to online learning during the COVID-19 outbreak and to determine the type of learning that students of the university will adopt after lifting the COVID-19 containment measures (post-COVID-19). Many past studies have found that students' perceptions of online learning are more positive than negative (Betancourt-Odio et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to investigate university students' perceptions towards the rapid passing to online learning during the COVID-19 outbreak and to determine the type of learning that students of the university will adopt after lifting the COVID-19 containment measures (post-COVID-19). Many past studies have found that students' perceptions of online learning are more positive than negative (Betancourt-Odio et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The main concern is the lack of digital skills of teachers in this area, which generates insecurities when carrying out meaningful educational strategies. The study carried out by Betancourt-Odio et al [21] confirms that there is a need to develop training related to digital skills that can explore beyond the selection and adaptation of digital resources so that teachers develop security in this area and can innovate through new technologies. Teachers require training to help them overcome this need for knowledge.…”
Section: Discussionmentioning
confidence: 95%
“…For the generation of knowledge about rural schools to become a solid collaborative base, research has a strategic role to play [60][61][62]. Leaders of rural school organizations, administrative decision-makers and politicians in rural areas receive through it evidence that can influence decision-making and favour the construction of paradigms.…”
Section: Rural Schools and Their Affectivity In The Management Of Sdg...mentioning
confidence: 99%